2021
DOI: 10.1111/jac.12547
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the advancement of chilling tolerance breeding in Northeast China

Abstract: Despite global warming, chilling injury during the reproductive stage is still a severe climate stress in temperate rice production systems. Much work has been done on stress avoidance by altering sowing dates and cultivar maturation, but stress tolerance has received less attention. The lack of data to inform existing genetic differences in chilling tolerance impedes model-based investigations exploring this adaptation.Here, from multiple data sources, we composited control experiments of 25 major rice cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Exposure to cold stress during the seedling, flowering, and grain-filling stages in rice was found to weaken the efficiency of light utilization in the leaves at these stages, lower the photosynthetic rate in rice leaves, inhibit the synthesis and transport of assimilates, affect the growth rate of rice, and cause an increase in the source/sink growth ratio, leading to a reduction in rice production [4]. Similar results were also found in other studies of rice subjected to cold stress at different growth stages [5,6]. The occurrence of late spring coldness during the rice seedling stage severely affects the safe production of rice.…”
Section: Introductionsupporting
confidence: 80%
“…Exposure to cold stress during the seedling, flowering, and grain-filling stages in rice was found to weaken the efficiency of light utilization in the leaves at these stages, lower the photosynthetic rate in rice leaves, inhibit the synthesis and transport of assimilates, affect the growth rate of rice, and cause an increase in the source/sink growth ratio, leading to a reduction in rice production [4]. Similar results were also found in other studies of rice subjected to cold stress at different growth stages [5,6]. The occurrence of late spring coldness during the rice seedling stage severely affects the safe production of rice.…”
Section: Introductionsupporting
confidence: 80%
“…In recent years, the cultivation of rice, one of the most important food crops feeding nearly half of the world’s population, has been threatened by abnormal environmental temperatures (such as chilling) induced by global climate change ( 1 , 2 ). The bottleneck limiting rice-planting region expansion to northern areas with much lower yearly temperatures is the improvement of chilling tolerance for rice cultivars, because rice is sensitive to chilling and the ability to tolerate low temperature is pivotal for its survival.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling degree days is a comprehensive index that factors in both the duration and intensity of chilling (Shimono et al, 2007) and could reflect the dynamic effect of low temperature on crop yield and yield components (Shimono, 2011; Zhang et al, 2021). In this study, we found statistically significant correlations between grain yield per plant as well as spikelet fertility and CDD for the continuous and intermittent chilling treatments at the booting and flowering stages.…”
Section: Discussionmentioning
confidence: 99%